The utilization of sugarcane bagasse, cassava peels and corn husks in handmade paper production - Aminah Asngad; Santhyami Santhyami; Ardiyana Rahma Pertiwi; Carissa Rahmitasari (STKIP Persada Khatulistiwa Sintang, 2021)
High demands for trees as the raw material of paper can disrupt the stability of the environment. It is necessary to find alternatives from other materials which are more environmentally friendly. This study aims to determine the quality of paper made from combining sugarcane bagasse with cassava peels or with corn husks using PVAc or tapioca starch adhesives. A completely randomized 2 x 2 factorial design with five times replication was used. The parameters tested were the tensile and tear resistance of the paper using a micrometer and a universal testing machine. A sensory analysis from panelists was also conducted. The combination of J1P1 produced a paper with the highest tensile strength (11.30 MPa) and the highest tear strength (1.82 MPa). The combination of J2P2 produced a paper with the lowest tensile strength (10.35 MPa) and the lowest tear strength (1.62 MPa). Variance analysis showed that the type of adhesive used showed a significant result on both tensile and tear resistance but material choices and interaction between materials and adhesive choices was not significantly different from the result on both tensile and tear resistance. Sensory testing shows that the combination of J1P1 was preferred the most. It can be concluded that the combination of J1P1 appeared to be the best combination.Keywords: Handmade paper, sugarcane bagasse, cassava peels, corn husk, PVAc tapioca starch, adhesive